Towards a Theory of the Direct-Indirect Tax Mix - Robin Boadway; Maurice Marchand; Pierre Pestieau (Queen's University, Department of Economics, 1992)
Despite the fact that all developed economies levy broadly-based indirect taxes alongside direct taxes, little theory is devoted to explaining the direct-indirect tax mix. Our purpose is to show that if different taxes have different evasion characteristics, some optimal tax mix emerges naturally. Assuming that only income tax can be evaded and focusing on a two-class economy, we analyze the case for supplementing optimal(nonlinear) income taxation with commodity taxation, and we develop conditions under which the latter should or should not be uniform.
Keywords: H21; H24; H26; 330